The influence of motivation in the development of reading skills in students attending 8th year of basic education at Inepe High School during the school year 2012-2013 - Salgado Jaya, Gabriela Paola (2014)
This project provides a research on motivation in the development of reading skills in a second language focusing our attention on students from eighth year of basic education. In part one; it describes briefly the background of this study, problem identification, research question and objectives. In part two, it contains the theoretical frame detailing and summarizing all information found about motivation and reading skills. It is divided in three chapters.